Gold Occurrence and the Effect of Roasting Temperature on Cyanidation Recovery from the Gold Acres Deposit, Lander County, Nevada - R. D. Osmanson (The Minerals, Metals and Materials Society, 1987)
A series of batch roasting tests was performed on minus 1/2 inch gold bearing refractory samples from the Gold Acres deposit, and 67 select particles were polished and the sulfide alterations were examined microscopically. The suite of specimens represents two hour batch roast treatments at 600°C, 700°C, 725°C, 750°c, 800°C, and 900°C. Auriferous pyrites were found to alter sequencially to pyrrhotite, magnetite and finally to hematite. It was found that the decrease in cyanidation extraction with high temperature roasting is likely due to the increas ing stability of magnetite and more crystalline hematite, and the decrease in porosity with these phases which occlude the gold. Gold has been noted to occur very early in the mineralizing sequence, with gold being found in quartz and in clay/carbonate rock matrix. No gold was found in the two pyrite phases, but numerous gold grains were found in pyrrhotite after pyrite and in subsequent iron oxides. Gold mineralization had apparently ended by the time base metals were introduced into the deposit.